2012
DOI: 10.1103/physreve.86.011931
|View full text |Cite
|
Sign up to set email alerts
|

Randomly evolving idiotypic networks: Modular mean field theory

Abstract: We develop a modular mean field theory for a minimalistic model of the idiotypic network. The model comprises the random influx of new idiotypes and a deterministic selection. It describes the evolution of the idiotypic network towards complex modular architectures, the building principles of which are known. The nodes of the network can be classified into groups of nodes, the modules, which share statistical properties. Each node experiences only the mean influence of the groups to which it is linked. Given t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Given these values, the influx probability p remains as main control parameter. In previous work (60, 61), we have studied a range for p from 0 to 0.1 and found that the architecture, which is of interest here evolves for p from 0.026 to 0.078. The results presented here explicitly are for p close to 0.078, where it is easier to initiate a reorganization of the pattern, but we have also studied a broader range of p .…”
Section: The Modelmentioning
confidence: 89%
See 4 more Smart Citations
“…Given these values, the influx probability p remains as main control parameter. In previous work (60, 61), we have studied a range for p from 0 to 0.1 and found that the architecture, which is of interest here evolves for p from 0.026 to 0.078. The results presented here explicitly are for p close to 0.078, where it is easier to initiate a reorganization of the pattern, but we have also studied a broader range of p .…”
Section: The Modelmentioning
confidence: 89%
“…The groups are built from clones of different idiotypes, which have an individual dynamics but share certain statistical properties. The building principles of these architectures can be described analytically (59, 60), and the statistical properties can be calculated within a mean-field theory in good agreement with simulations (61). …”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations